Al-Adab Al- ‘Araby Fi Fatrah Intiqal Al- Hukmi Min Khilafah Al- Umawiyyah Ila Khilafah Al-‘Abbasiyyah (Dirasah Washfiyyah Tarikhiyyah Adabiyyah) - Dien Nur Chotimah (Journal of Arabic Literature (JaLi), 2019)
The period of Arab literature was divided into the political age, the pre-Islamic period, the Islamic era, the Umayyad era, the Abbasia era, the Andalusian era, the era of the Mamalik, and the modern era. Because of the Umayyah caliphate and the Abbasia caliphate, the long period of politics extends. Political problems emerged from within the caliphate and therefore have a lot to do with Arab literature. The researcher used the descriptive and historical method. The result of this research on the characteristics of the Arabic literature in the period between the Umayyah and Abbasia Caliphate, are: 1) The poetry expresses the conditions obtained from the historical facts of war, 2) encouraging in its later stages, 3) the use of clear words and structures in the body Poem and poetry.Keywords: Arab literature, period of transition of government, Umayyah caliphate, Abbasih caliphate